Chemical constituents from methanolic extract of Garcinia mackeaniana leaves and their antioxidant activity - Ha, Nguyen Thi Thu; Cuong, Pham Van; Tra, Nguyen Thanh; Anh, Le Thi Tu; Cham, Ba Thi; Son, Ninh The (Vietnam Journal of Science and Technology, 2020)
A phytochemical investigation of the methanolic extract of Garcinia mackeaniana leaves led to the isolation, and determination of five secondary metabolites, including one benzophenone 4,3',4'-trihydroxy-2,6-dimethoxybenzophenone (1), two flavone C-glucosides vitexin (2) and its 2''-O-acetyl derivative (3), one biflavone amentoflavone (4), and one mono-phenol methyl protocatechuate (5). The chemical structures of these compounds were characterized by the NMR-spectroscopic method. These isolated compounds were isolated from G. mackeaniana species for the first time. Benzophenone derivative 1 has shown to be associated with a significant IC50 value of 14.97±0.8 µg/mL in the DPPH-antioxidant assay.